Regime de escoamento do Rio Uruguai no trecho entre a hidrelétrica de Foz do Chapecó e o Salto do Yucumã - Pasini, Fernando (2019)
The Uruguay River, due to its hydrodynamic and topographic characteristics, is considered one of the main national water courses for hydroelectric use and, consequently, subject to the impacts resulting from the installation of these activities. Considering the importance of the hydrological characterization of the hydroelectric downstream areas, this work aimed to diagnose the impact of the operation of the Foz de Chapecó Hydroelectric Plant (HPP) on the Uruguay River flow regime in the reach between the HPP and the Yucumã Falls. For this, the fluviometric information was collected and interpreted in the area delimited for study. The interpretation was performed using the IHA 7.1 software (Indicators of Hydrological Alterations), which were submitted to series collected by the Iraí fluviometric station (74100000), the oldest of the region, the date series were sampled in many diferente ways, allowing the indication of the representativeness that each series has, as well as a detailed indication of the impacts that are occurring in the period after the installation of the HPP. Information was also collected from the fluviometric station of Foz do Chapecó Downstream (74050000), Itapiranga (74329000) and an experimental monitoring station was installed in Yucumã Fall, which, together with those of Iraí, enabled an indication of how the flow in the reach between the HPP and the Yucumã Fall, providing, also, the estimation of the propagation time of the flood pulses, fundamental for the management of the basin. It was verified that the analysis of a flow data series composed of only one daily information is not the most representative model of the impacts that occur in the Uruguay River, presenting them in an attenuated way. The use of the IHA software was satisfactory in the analysis of the hydrological alterations in the HPP post, among them the great variability of the daily flow and the regularization of the flow, which maintains normally higher levels, and considerably altering the peaks of drought. As for the regime of flow and propagation of the daily waves caused by the operation of the HPP, it is indicated that there is an average delay of 17:22 h of propagation through the study section (140 km). In Foz do Chapecó, the daily peak-peak is felt around 3:56 h, in Iraí at 6:24 h. of the same day, in Itapiranga at 5:54 h. and in the Yucumã Fall at 9:18 p.m., both of following day. Although the HPP follows the model of operation imposed by the National Water Agency, the flow characteristics verified by this study make the region a place of great environmental fragility.